Anterior cruciate ligament reconstruction using patellar tendon versus hamstring tendon: a prospective comparative study with 9-year follow-up - Wipfler, Benjamin Gerhard Tobias; Donner, Stefanie; Zechmann, Christian; Springer, Jan; Siebold, Rainer; Paessler, Hans Heinrich (Arthroscopy, 2011)
Purpose - To analyze the long-term evaluation of clinical, functional, and magnetic resonance imaging (MRI) results after implant-free press-fit anterior cruciate ligament (ACL) reconstruction with bone-patella tendon (BPT) versus quadrupled hamstring tendon (HT) grafts. - Methods - Sixty-two ACL-insufficient patients were included in a prospective, randomized study (31 BPT and 31 HT). Both surgical procedures were performed without any implants by a press-fit technique by the senior author. The femoral tunnel was drilled through the anteromedial portal for anatomic placement. At 8.8 years after reconstruction, 53 patients (28 BPT and 25 HT) were examined by different clinical and functional tests. Bilateral MRI scans were performed and interpreted by an independent radiologist. - Results - On follow-up, the score on the International Knee Documentation Committee evaluation form was significantly better in the HT group. The clinical examination including range of motion, KT-1000 test (MEDmetric, San Diego, CA), and pivot-shift test showed no significant differences. On isokinetic testing, the mean quadriceps strength was close to normal (96%) in both groups, but the hamstring strength was lower in the HT group (100.3%/95.1%). Kneeling (1.5/1.1, P = .002), knee walking (1.72/1.14, P = .002), and single-leg hop test (95.8%/99.1%, P = .057) were better in the HT group. The MRI findings about the mean degree of cartilage lesion (International Cartilage Repair Society protocol) of the operated (2.1/2.1) and nonoperated (1.4/1.8) knee showed no significant differences. No significant difference was found in the grade of medial or lateral meniscal lesion or the number of patients having meniscal lesions when the operated and nonoperated knees were compared. Tunnel measurements, Caton-Deschamps Index, and the sagittal ACL angle were similar. - Conclusions - The implant-free press-fit technique for anterior cruciate ligament reconstruction by use of bone-patellar tendon and hamstring grafts with anatomic graft placement is an innovative technique to preserve the cartilage and meniscal status without significant differences between the operated and nonoperated knees in the long term. Significantly less anterior knee pain was noted in the hamstring group, when testing for kneeling and knee walking. - Level of Evidence - Level II, prospective comparative study.